Pertussis infection in adolescents and adults with persistent cough: A Review (Bangladesh Journal of Medical Microbiology, 2011)
Pertussis or whooping cough, generally considered as the disease of infants and children, is an acute respiratory tract disease responsible for around 300,000 deaths annually. However, recent reports from many countries of the world clearly indicate that people of all age groups including adolescent and adults could be suffering from this disease. Pertussis remains an underestimated and under reported disease in adolescent and adults due to atypical symptoms in these age groups. Moreover, pertussis has been re-discovered as a frequent cause of prolonged cough in adolescents and adults in the recent past but the diagnosis still is often missed unless specific diagnostic tests are applied. The affected adolescents and adults act as reservoirs of the disease to the vulnerable population of infants. There have been increasing reports of pertussis outbreaks in adults population in many western countries and vaccination of this group is being planned. Additional booster doses of acellular pertussis vaccine may help to control and prevent pertussis.DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15819 Bangladesh J Med Microbiol 2011; 05 (01): 31-34